Use of chest imaging in the diagnosis and management of COVID-19: a WHO rapid advice guide - Akl, Elie A.; Blažić, Ivana; Yaacoub, Sally; Frija, Guy; Chou, Roger; Appiah, John Adabie; Fatehi, Mansoor; Flor, Nicola; Hitti, Eveline; Jafri, Hussain; Jin, Zheng-Yu; Kauczor, Hans-Ulrich; et al. (Radiology, 2021)
The World Health Organization (WHO) undertook the development of a rapid guide on the use of chest imaging in the diagnosis and management of coronavirus disease 2019 (COVID-19). The rapid guide was developed over 2 months by using standard WHO processes, except for the use of “rapid reviews” and online meetings of the panel. The evidence review was supplemented by a survey of stakeholders regarding their views on the acceptability, feasibility, impact on equity, and resource use of the relevant chest imaging modalities (chest radiography, chest CT, and lung US). The guideline development group had broad expertise and country representation. The rapid guide includes three diagnosis recommendations and four management recommendations. The recommendations cover patients with confirmed or who are suspected of having COVID-19 with different levels of disease severity, throughout the care pathway from outpatient facility or hospital entry to home discharge. All recommendations are conditional and are based on low certainty evidence (n = 2), very low certainty evidence (n = 2), or expert opinion (n = 3). The remarks accompanying the recommendations suggest which patients are likely to benefit from chest imaging and what factors should be considered when choosing the specific imaging modality. The guidance offers considerations about implementation, monitoring, and evaluation, and also identifies research needs.Published under a CC BY 4.0 license.Online supplemental material is available for this article.
Published online: Jul 30 2020
Gesehen am 11.08.2021